Impact of a prophylactic combination of dexamethasone–ondansetron on postoperative nausea and vomiting in obese adult patients undergoing laparoscopic sleeve gastrectomy during closed-loop propofol–remifentanil anaesthesia: A randomised double-blind placebo-controlled study. Issue 12 (December 2016) - Bataille, Aurélien; Letourneulx, Jacques-Florian; Charmeau, Alain; Lemedioni, Pascale; Léger, Philippe; Chazot, Thierry; Le Guen, Morgan; Diemunsch, Pierre; Fischler, Marc; Liu, Ngai
Abstract : BACKGROUND: In obese patients, the incidence of postoperative nausea and vomiting (PONV) following sleeve gastrectomy under titration of total intravenous anaesthesia (TIVA) and the relevance of risk factors to indicate prophylaxis is unknown. OBJECTIVES: The hypothesis was that after automated TIVA, prophylaxis reduces PONV following laparoscopic sleeve gastrectomy. Our objective was to determine the incidence of PONV and evaluate the efficacy of dexamethasone and ondansetron as prophylaxis when automated intravenous anaesthesia is employed. DESIGN: A randomised, placebo-controlled, single-centre, double-blinded study. SETTING: Secondary care centre in New Caledonia from June 2013 to January 2014. PATIENTS: A total of 122 patients were randomised and 117 (92 women) were included in the analysis (58 in the prophylaxis group and 59 in the placebo group). Eligibility criteria included at least two of the known risk factors for PONV: female sex, nonsmoking status, prior history of PONV or motion sickness and expected postoperative opioid analgesia. Exclusion criteria included disorders limiting the use of the bispectral index. INTERVENTIONS: All patients received propofol and remifentanil controlled by the same automated system during induction and maintenance of general anaesthesia. The controller modifies the calculated effect-site concentrations according to bispectral index values. Patients received either intravenous dexamethasone 4 mg after tracheal intubation and ondansetron 4 mg during skin closure, or placebo. MAIN OUTCOME MEASURES: The primary endpoint was the cumulative incidences of 24-h PONV and severe PONV (vomiting or nausea with a score of ≥4 on an 11-point verbal rating scale). Data are presented as percentage (95% confidence interval). RESULTS: PONV in the first 24 h occurred in 45 (34 to 60)% of patients who received prophylaxis and 54 (41 to 67)% in the placebo group ( P  = 0.35). The numbers of patients who suffered severe PONV [19 (10 to 32)% in the prophylaxis group vs. 20 (11 to 33)%, P  = 1, in the placebo group] and who required rescue antiemetic drugs [55 (41 to 68) vs. 63 (49 to 75)%, P  = 0.46] were similar between the groups. CONCLUSION: The combination of dexamethasone and ondansetron was not effective in preventing PONV or severe PONV in obese patients undergoing laparoscopic sleeve gastrectomy after TIVA. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT01876290.